الحماية الجنائية للأمن السيبراني في ضوء رؤية المملكة 2030 - الجمل، حازم حسن أحمد (كلية الملك فهد الأمنية - مركز الدراسات والبحوث, 2020)
تعالج هذه الدراسة حالات تدخل القانون الجنائي في مجال حماية الأمن السيبراني، وضوابطه، وصوره، وأهميته، وفاعليته، بالمعنى الواسع، وتشتمل على مجموع الأطر، والمفردات، والعناصر، والقيم، والأصول، والموجودات، والمقومات التنظيمية، والتقنية، والإدارية، والفنية، وهياكلها، وكوادرها، وأنشطة الإدارة، وأساليبها المختلفة، التي تتوصل من خلالها أي دولة إلى حماية فضائها السيبراني والدفاع عنه، كمظهر من مظاهر السيادة، وكضرورة تفرضها حتمية التحول والاندماج الرقمي على المستوى العالمي. وقد ركزت هذه الدراسة على استكشاف واقع الحماية الجنائية للأمن السيبراني (الموضوعي – الإجرائي) وفق أنظمة الدول الرائدة التي وضعت نظاما شاملا ومتكاملا لحماية أمنها السيبراني، بهدف إمكانية الاستفادة من منهج هذه الدول في الشأن السعودي، وبهدف تعزيز البيئة والاقتصاد. والاستثمار الرقمي في المملكة، بما يتوافق وطموحات المملكة حسب روية 2030 في جمال التحول الرقمي وتقنية المعلومات.
This study examines (cases, controls, aspects, importance and efficacy) of criminal law intervention in the field of cybersecurity in the board sense, including a combination of frameworks, vocabularies, components, values, assets, inventories, regulatory substantive, administrative and technical essentials, their structures and cadres, administration activities and different methods used by any country to protect and defend its cyberspace as an aspect of sovereignty and necessity for digital transformation and integration worldwide. This study focuses on exploring the reality of criminal protection of cybersecurity (substantive and procedural aspects) according to the leading countries systems that developed a comprehensive and integral system to protect their cybersecurity, with a view to possible avail the methodology of these countries in Saudi Arabia affairs, and to strengthen environment, economy and digital investment in KSA in line with aspirations of Saudi Arabia Vision 2030 in field of digital transformation and information technology.
Keywords: المسؤولية الجنائية -- الأمن السيبراني -- جرائم المعلوماتية -- رؤية المملكة 2030 -- السعودية